Life Skills in a Minute: Sewing on a Button - Heather M. Janney (EDIS, 2021)
Even though sewing a button back on is quite a simple task, many people refuse to try it simply because it seems too daunting. This publication will help you to understand the difference in button types and share the methods to be utilized in sewing a button on. Written by Heather Janney and published by the UF/IFAS 4-H Youth Development program; 3 pages. https://edis.ifas.ufl.edu/4h414